2021
DOI: 10.3897/neobiota.67.63846
|View full text |Cite
|
Sign up to set email alerts
|

Economic costs of invasive alien species in Mexico

Abstract: Invasive alien species (IAS) are a leading driver of biodiversity loss worldwide, and have negative impacts on human societies. In most countries, available data on monetary costs of IAS are scarce, while being crucial for developing efficient management. In this study, we use available data collected from the first global assessment of economic costs of IAS (InvaCost) to quantify and describe the economic cost of invasions in Mexico. This description was made across a range of taxonomic, sectoral and temporal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…There are generally few reports on the global economic impacts of invasive species in aquatic ecosystems (Lovell et al 2006). However, compared with the whole InvaCost database (Diagne et al 2020b), our estimates for these ecosystems are exceptionally high (but see the case of Mexico, Rico-Sánchez et al 2021). A global assessment of all data included in InvaCost reported that the monetary costs of aquatic invasive species only constituted 5% of the total reported costs.…”
Section: Regional Management and The Need For Effective National Coordination Of Actionsmentioning
confidence: 76%
See 1 more Smart Citation
“…There are generally few reports on the global economic impacts of invasive species in aquatic ecosystems (Lovell et al 2006). However, compared with the whole InvaCost database (Diagne et al 2020b), our estimates for these ecosystems are exceptionally high (but see the case of Mexico, Rico-Sánchez et al 2021). A global assessment of all data included in InvaCost reported that the monetary costs of aquatic invasive species only constituted 5% of the total reported costs.…”
Section: Regional Management and The Need For Effective National Coordination Of Actionsmentioning
confidence: 76%
“…This species, together with D. polymorpha or Neovison vison, which are amongst the ten costliest species in Spain, are also amongst the invasive aquatic species causing the most widespread economic impacts (Cuthbert et al 2021a). E. crassipes also seems to be one of the costliest species in several African countries, in Asia and in North American countries, such as Mexico (Diagne et al 2021b;Liu et al 2021;Rico-Sánchez 2021); while D. polymorpha seems to be very costly in the USA and N. vison in other European countries such as Germany (Crystal-Ornelas et al 2021;Haubrock et al 2021b). Being in the list of the 100 of the worst invasive species, D. polymorpha was also ranked as the 8 th costliest species of that list (Cuthbert et al 2021b).…”
Section: General Costs Of Ias In Spainmentioning
confidence: 99%
“…Island ecosystems are regarded as more vulnerable to invasion by alien species and their impacts 62 . They can incur economic costs through a different suite of sectors and species than mainland areas 64 . Islands are substantially more biodiverse than mainlands 65 .…”
Section: Discussionmentioning
confidence: 99%
“…Ricinus communis L. fruits were collected on public land where it grows wild in the city of Jerez (Zacatecas, Mexico), located at the latitude of 22°28′30″ N and longitude of 102°59′08″ W. This plant is considered an invasive exotic species in Mexico and other countries [ 21 , 22 , 23 ]. Therefore, a permit or regulation was not required for its collection.…”
Section: Methodsmentioning
confidence: 99%